Digital Natives and the Call for Innovation in Arabic Language Education - Achmad Nashichuddin; R. Taufiqurrochman; Nur Salam (Kitaba, 2025)
Abstract: Today’s graduate students in Arabic language education are unmistakably digital natives—predominantly young women (70.6%) aged 21–25, graduates of Islamic higher education institutions across Indonesia, and deeply embedded in digital culture. This study explores their research interests, academic expectations, and aspirations through a structured survey of 51 newly enrolled master’s students at Maulana Malik Ibrahim State Islamic University (UIN Malang). Findings reveal a decisive shift in scholarly orientation: 37.3% identified “technology and media in Arabic language education” as their primary research interest, far surpassing traditional domains like linguistics or literature. Their call for innovation is not merely technological but pedagogical—they seek curricula that integrate digital tools, emphasize practical application, and align with 21st-century competencies. Simultaneously, a significant academic preparedness gap emerges: 72.5% requested intensive training in scholarly writing, and 64.7% demanded access to international journals, signalling a need for methodological scaffolding. Global aspirations are equally strong, with multiple students explicitly advocating for student exchange programs to Saudi Arabia, Malaysia, and Madinah. Thematic analysis of open-ended responses yielded five strategic priorities: (1) strengthening academic capacity, (2) advancing internationalization, (3) ensuring curriculum relevance in the digital era, (4) improving internal management, and (5) nurturing an Islamic scholarly vision that fuses linguistic mastery with civilizational mission. This study argues that the voices of digital-native students are not peripheral feedback but central diagnostic data for transforming Arabic language education into a dynamic, responsive, and globally engaged discipline in the Global South.